Performance of Dye-Sensitized Solar Cell Using Size-Controlled Synthesis of TiO2 Nanostructure - Talib, A.; Ahmad, M. K.; Ahmad, N.; Nafarizal, N.; Mohamad, F.; Soon, C. F.; Suriani, A. B.; Mamat, M. H.; Murakami, K.; Shimomura, M. (International Journal of Integrated Engineering, 2020)
Titanium dioxide (TiO2) or titania shows a great interest in solar cell application due to its morphology and crystalline structure. Moreover, it is an affordable compound that could make solar cells more cost economical than traditional silicon solar cells. In this study, one-step hydrothermal method is demonstrated to synthesis rutile TiO2 nanorods and nanoflowers morphology in nanoscale dimension on different hydrothermal reaction times for Dye-sensitized solar cells application. Increasing the reaction time could influence in formation of higher crystalline rutile phase titania nanostructure before abruptly decreases as the prolong hydrothermal process carry out. The length of the nanorods produced shows increasing behaviour and the growth of nanoflowers are become denser obviously. Band gap estimation is 2.75 eV slightly lower than bulk rutile TiO2. It shows that the growth mechanism under different reaction times has great influences on the morphologies and alignment of the nanostructure. Further, the DSSCs fabricated using 15 hours reaction time exhibited the best photovoltaic performance with highest efficiency of 3.42% and highest short-circuit photocurrent of 0.7097V.